2016
DOI: 10.1242/jeb.134759
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent benefits of bacterial exposure in embryonic development of Daphnia magna resting eggs

Abstract: The environments in which animals develop and evolve are profoundly shaped by bacteria, which affect animals both indirectly through their role in biogeochemical processes and directly through antagonistic or beneficial interactions. The outcomes of these activities can differ according to environmental context. In a series of laboratory experiments with diapausing eggs of the water flea Daphnia magna, we manipulated two environmental parameters, temperature and presence of bacteria, and examined their effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…If the necessary beneficial microbiota are transmitted by the parent into the resting stage, then the micro‐organisms can be considered a form of parental effect or a source of heritable nongenetic variation in their host (Badyaev & Uller, ; Zilber‐Rosenberg & Rosenberg, ). The occurrence of microbial transmission through resting stages would also support the often untested assumption that the microbial symbionts are deriving a benefit from the association (Mushegian & Ebert, ), since host and symbiont reproduction would be linked across host generations. Where the host is dependent on acquiring beneficial microbes from the environment after dormancy, we would expect low taxon‐specificity in the host–microbe association, because selection would disfavour reliance on specific microbes whose presence is not guaranteed in the environment where hatching occurs.…”
Section: Introductionmentioning
confidence: 83%
“…If the necessary beneficial microbiota are transmitted by the parent into the resting stage, then the micro‐organisms can be considered a form of parental effect or a source of heritable nongenetic variation in their host (Badyaev & Uller, ; Zilber‐Rosenberg & Rosenberg, ). The occurrence of microbial transmission through resting stages would also support the often untested assumption that the microbial symbionts are deriving a benefit from the association (Mushegian & Ebert, ), since host and symbiont reproduction would be linked across host generations. Where the host is dependent on acquiring beneficial microbes from the environment after dormancy, we would expect low taxon‐specificity in the host–microbe association, because selection would disfavour reliance on specific microbes whose presence is not guaranteed in the environment where hatching occurs.…”
Section: Introductionmentioning
confidence: 83%
“…Studies in Daphnia magna indicate that host-associated bacterial communities are generally required for survival, reproduction, and nutrition [ 16 ]. Daphnia- associated bacteria also influence ecologically relevant traits such as tolerance to cyanobacteria [ 17 , 18 ], host embryonic development [ 19 ], and overall ecological success [ 20 ]. The community composition of gut bacteria in D. magna is influenced by both the host genotype and by a variation in environmental bacteria [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paleo-genetic reconstruction studies suggest that the genetic architecture of Daphnia populations varies by sediment depth and reflects responses to environmental stressors over time [ 27 ]. The bacterial communities associated with Daphnia -resting eggs deposited in the sediment have a beneficial effect on the survival of Daphnia hatched from those eggs, and may be required for the establishment of clonal lines [ 19 ]. However, no studies so far have utilized naturally occurring genetic variation among Daphnia across sediment depth to address host genotypic variation as a determinant of composition of bacterial communities in Daphnia .…”
Section: Introductionmentioning
confidence: 99%
“…A similar report also showed that a Pseudomonas strain isolated from a D. magna host is beneficial to the development of D. magna resting eggs at warm conditions. 84 Under mercury stress, lower survival rates were observed for the three mercury-treated groups when compared to their counterparts at the end of the assay (day 18): Bac-Suppl + Hg (43%, n = 13/30), Pse-Inf + Hg (70%, n = 21/30), and Bac- Free + Hg (60%, n = 18/30). Daphnids from the Bac-Suppl + Hg were most severely affected under mercury stress (χ 2 = 17.22, p < 0.0001) while the survival rates of Pse-Inf + Hg daphnids were statistically similar to those of Pse-Inf daphnids (χ 2 = 2.18, p = 0.14).…”
Section: Environmental Science and Technologymentioning
confidence: 85%